IMPACT OF SOCIAL MEDIA IN CREATING AWARENESS AND DISSEMINATION OF INFORMATION DURING ‘JANTA CURFEW’ OBSERVED IN THE SCENARIO OF COVID-19: AN ANALYSIS - Ankit Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Media plays the role of magic multiplier and social media has the power to make the information from public to private and private to public in the e-society. During the disaster, emergency crisis and with the challenge of maximum participation social media is always beneficial. People want the active participation in current scenario either they are in the house or out of boundary. This study examines and analyzes the impact and true role of social media during the emergence of pandemic especially in a largest democracy and developing nation like India. This is also establishing and highlighting the great communication link of healthcare and political communication with the open eye of social media users. They aren’t just reacting and participating but also finding the lives and survival in the disaster of pandemic with the great faith on nation’s leader and following voluntarily curfew.